Common sports-related infections: a review on clinical pictures, management and time to return to sports - Ahmadinejad, Z.; Alijani, N.; Mansori, S.; Ziaee, V. (Asian Journal of Sports Medicine, 2014)
There is a relationship between exercise and changes in immunity. So athletes are prone to different medical problems such as injuries and infections. Infection is an important medical problem which could be a reason for athletes` absence from training. The relationship between physical activity and immune system, characteristics of different types of infections in athletes with emphasis on special clinical presentations or complications, time to return to physical activity and training and strategies to prevent development and transmission of infections in athletes or physically active people are the main topics of this review.